2016
DOI: 10.1186/s12878-016-0070-8
|View full text |Cite
|
Sign up to set email alerts
|

Anaemia and its association with month and blood phenotype in blood donors in Fako division, Cameroon

Abstract: BackgroundAnaemia is one of the main factors in the deferral (disqualification) of blood donors following haematological screening. There is paucity of data on the prevalence of anaemia in blood donors in Sub-Saharan Africa. This study was undertaken to determine the prevalence of anaemia and its association with month and blood phenotype in blood donors in Fako division of Cameroon.MethodsBlood donors were recruited between the 1st of January and 31st of December 2014, and their haemoglobin concentration (Hb)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 15 publications
1
12
1
Order By: Relevance
“…For example, the increased risk of LHD in females compared with males was significantly higher in studies from Africa (OR 5. 24…”
Section: Sexmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the increased risk of LHD in females compared with males was significantly higher in studies from Africa (OR 5. 24…”
Section: Sexmentioning
confidence: 99%
“…LHD by age (years) was reported in 19 new studies [9,10,12,15,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. In 14 studies which reported results separate for men and women, the general trend across studies for men was for LHD rates to increase with age (Figure 4), whereas for women there were fewer deferrals among women over 50 compared to women younger than 50.…”
Section: Agementioning
confidence: 99%
See 1 more Smart Citation
“… 12 Anemia is a common manifestation in SSA, especially in children and pregnant women, and malaria is one of its major causes. 52 HIV, on the other hand, infects and depletes CD4 + T cells, thereby exposing infected patients to opportunistic infections. HIV is also associated with dysregulation of proinflammatory cytokines and chemokines in plasma and lymph nodes, thereby influencing disease progression.…”
Section: Impact Of Mhc In Ssamentioning
confidence: 99%
“…The issue of young age of donors and health, as well as adverse effect of donation, was little studied in LMICs (Bahadur et al ., ). Anaemia (<13 g dL −1 for male and <12 g dL −1 for females) is the most common cause of donor deferral, particularly in women (30% in Cameroon, Kwenti & Kwenti, ; 27% in Libya, Abud et al, ) and was more frequent in females. However, there was no evidence that the current eligibility criteria (12·5 g dL −1 ± 0·5 and 50 kg) increased the number of adverse post‐donation events.…”
Section: Resultsmentioning
confidence: 99%